La influencia de factores sistémicos en el uso de las prótesis totales - Lima Chaves, Carolina de Andrade [UNESP]; Zardo Trindade, Flávia [UNESP]; Sgavioli Massucato, Elaine Maria [UNESP]; Mollo Junior, Francisco de Assis [UNESP]; Compagnoni, Marco Antonio [UNESP] (My University, 2009)
According to the possible influence of systemic diseases and of drugs used for its treatment in buccal cavity, the aim of present study is to carry out a review of literature on this topic, emphasizing on influence of these factors on use of the total prostheses (PTs), allowing to surgeon-dentist a better scientific knowledge to creation of this type of rehabilitation treatment.
Influence of systemic factors in use of total prostheses
Keywords: Disease; Patients; Total dental prosthesis